Induction of In Vitro Culture of Potato Microtuber by Using Alar and Dark Photoperiod Application - Dwiati, Murni; Anggorowati, Sulastri (AGRIVITA Journal of Agricultural Science, 2011)
Providing virus free potato seeds in order to increase potato production in Indonesia could be carried out by using microtuber resulting from microcutting. The growth of single node microcutting potato can initiate microtuber formation when growth inhibiting substances such as alar in combination with dark photoperiod treatment is applied. This study was aimed to elucidate the effect of alar and dark photoperiod on the date of microtuber emergence and production. The experiment was arranged in a factorial Randomized Completely Block Design in which alar concentrations i.e. 0, 10-3, 5 x 10-3, and 10-2 mg/L, served as factor I, and dark photoperiods i.e. 16, 20, and 24 hrs/day, were used as factor II. Each treatment combination was replicated three times giving rise to 36 experimental units. Data were analyzed using ANOVA (F test) followed by Duncan Multiple Range Test (DMRT) when significant effect of the treatments existed. The results showed that alar and dark photoperiod affected individually on the date of microtuber emergence, while the best alar concentration to increase microtuber production was 10-3 mg/L with 10.67 microtubers/cutting. Dark period has no significant effect on the induction of potato microtuber. Keywords: potato microtuber, alar, dark photoperiod